Immunomodulatory effects of immune cell-derived extracellular vesicles in melanoma - Nanru, Peng (Frontiers in Immunology, 2024)
Melanoma, recognized as one of the most immunogenic malignancies in humans, holds paramount significance in the realm of immunotherapy. However, the emergence of drug resistance and the occurrence of adverse drug reactions underscore the pressing need to explore increasingly personalized immunotherapeutic modalities. Extracellular Vesicles (EVs), pivotal derivatives of immune cells, assume pivotal roles by encapsulating proteins, lipids, and nucleic acids within bilayer lipid structures, thereby facilitating targeted delivery to other immune cells. This orchestrated process orchestrates critical functions including antigen presentation, immune modulation, and the induction of apoptosis in tumor cells. A burgeoning body of evidence underscores the vast therapeutic potential of EVs in melanoma treatment. This comprehensive review aims to delineate the roles of EVs derived from immune cells such as dendritic cells, natural killer cells, macrophages, and T cells in the context of melanoma patients, thereby furnishing invaluable insights for the future direction of melanoma immunotherapy.